الابتكار في تعليم اللغة العربية القائم على المجلات العلمية: تعزيز مهارات التفكير النقدي والقراءة الأكاديمية في العصر الرقمي: Innovation in Arabic language teaching based on scientific journals: Improving critical thinking and academic reading skills in the digital era. - Puji Rahayu (Study Program of Arabic Language Education (PBA), 2026)
This study aims to analyze the effectiveness of scientific journal-based Arabic language learning in improving students' academic literacy and critical thinking skills in the digital age. The research method used was a mixed methods approach with a descriptive-qualitative approach and a simple experiment on Arabic Language Education students at three Islamic universities in Indonesia. Data were collected through observation, questionnaires, interviews, and analysis of student journal documents. The results indicate that journal-based learning can improve critical reading and academic writing skills in Arabic, as well as strengthen understanding of scientific text structure. Implementation of this learning strategy also fosters learning motivation and collaboration among students through discussions based on current literature. This study recommends integrating journal-based learning into the Arabic Language Education curriculum to develop students' academic and professional competencies in the 21st century.